Teaching Methods and Learning Motivation for Population Knowledge and Environmental Concern - Nurdin; Tjipto Djuhartono; Rani Noviyanti; Iwan Budiarso; Nani Hanifah (LPPM Undiksha, 2024)
The low motivation to learn and students' knowledge about population and the environment affects students' concern for the environment and population problems. So, a solution is needed to improve students' attitudes, namely through effective learning methods. This study aimed to test the differences in population knowledge and environmental awareness using discussion teaching methods and lecture teaching methods to students with high learning motivation and those with low learning motivation. This study used a quasi-experimental design with a 2x2 factorial design. The study's subjects were a group of 80 students consisting of 40 students with high learning motivation and 40 with low learning motivation for grade 12. Data on population knowledge and environmental awareness was collected using an objective test instrument with the answer choices True (B) with a score of 1 and False (S) with a score of 0. After the data was collected, it was analyzed using two-way variance analysis and the Tukey test. The results of the study revealed that there are significant differences between the two teaching methods, where the discussion teaching method is more effective than the lecture teaching method, the lecture teaching method is better used in learning groups with high learning motivation, the discussion teaching method is better used in learning groups with low learning motivation, there is an interaction effect between teaching methods and learning motivation on population knowledge and environmental awareness, where high learning motivation, the lecture teaching method is better used than the discussion teaching method, but there is a reverse tendency for low learning motivation.